Looking after children without parents and encouraging their social integration: a Latvian perspective - Inese Jurgena; Zigurds Mikainis (Scottish Journal of Residential Child Care)
Integration is a reality of the contemporary world. The concept 'integration' is defined as 'a process where different elements are combined together in one community, while each of these elements preserves its own basic identity' (Pabriks, Vēbers, Āboliņš, 2001, p.6). Social integration is seen as crucial to the development of the Latvian state, because such integration should encourage everyone in society to take a tolerant, considerate and understanding view of other people. It appeals to the person to become a creator of subjective relationships and not to be indifferent to the plight of others who may be less fortunate. In short, social integration is seen as a key to the promotion of children's rights.